23 Cryopreservation of human amniotic membrane (HAM) for ocular surface reconstruction: a comparison beetween protocols. (16th November 2022) - Bertolin, Marina; Gassa, Sebastiano Dalla; Trojan, Diletta; Spagnol, Lisa; Donisi, Pietro Maria; Camposampiero, Davide; Ponzin, Diego; Ferrari, Stefano
Abstract : Purpose: In the past decades, the human amniotic membrane has been largely applied for several surgical and non-surgical procedures. It has been farther demonstrated that both hAM and cornea share similar patterns of expression of structural components of the basement membrane (like laminin 5 and collagen IV) making hAM an useful tissue for ocular surface reconstruction. Since 1996 in fact, amniotic membrane transplantation has been applied to a large number of ocular surface diseases including Stevens-Johnson syndrome, pterygium, corneal ulceration, ocular surface reconstruction after chemical/thermal burns and in the reconstruction after excision of ocular surface neoplasia. During the previous decades, hAM has achieved a pivotal role in regenerative medicine too. The possibility to preserve human amniotic membrane, without affecting membrane's features, has become pivotal, allowing virological and microbiological analyses to be carried out before grafting. The purpose of the present study is to investigate an easier and cheaper protocol for human amniotic membrane preservation without affecting its properties and structure, ensuring the safety profile of the tissue. We compared the effects on adhesive and structural properties of newer preservation conditions to those obtained with an established, standardized protocol (dimethyl sulfoxide at -160°C). In attempt to simplify and enhance the safety of the procedure, we tested dextran-based freezing medium and a dry condition (no medium) at temperatures of -80°C. Methods: Five patches of human amniotic membrane were obtained from three different donors. For each donor, five preservation condition were tested: dimethyl sulfoxide at -160°C, dimethyl sulfoxide at -80°C, dextran-based medium at -160°C, dextran-based medium at -80°C and dry freezing at -80°C (no medium). At the end of four months storage period, adhesive properties and structure were analyzed. Results: None of the newer preservation protocols showed differences in adhesive and structural properties of the tissues. The stromal layer always kept its adhesiveness, while both structure and basement membrane were not altered by any the preservation protocol. Conclusions: Switching from liquid nitrogen cryopreservation to -80°C would reduce manipulation, simplify the procedure, making it also cheaper. The use of dextran-based freezing medium or no medium at all (dry condition) would avoid the potential toxicity of the dimethyl sulfoxide-based freezing media.